A study of domestication and foreignization strategies in two English translated editions of Liao Zhai Zhi Yi / Liu Gong - Liu , Gong (2017)
Based on the dichotomy of culture-oriented translation strategies—domestication and foreignization coined by Venuti in 1988, the present research aims to explore the procedures underneath the two translation strategies applied by translators to render the cultural elements in classical Chinese, and also attempts to find the readers’ reception towards the two main strategies. Therefore, research questions are devised to find the dominant strategy to treat the cultural specific items in two English translations of Chinese classical work Liao Zhai Zhi Yi, and the participants’ reception towards the two main strategies via their evaluation of the translations’ adequacy, comprehensibility and their personal preference. Being both text-oriented and reader-oriented, the current research employs a qualitative approach to describe and analyze the translation procedures in the corpus and the data of readers’ reception. The findings conclude that the first translation is foreignization-oriented and the second one is domesticationoriented; according to the perception of participants, foreignization is a more ideal strategy to make the target text more faithful and preferable to translate the cultural elements in classical Chinese literature.